2019 Proceedings of the Sixteenth Workshop on Analytic Algorithmics and Combinatorics (ANALCO) 2019
DOI: 10.1137/1.9781611975505.2
|View full text |Cite
|
Sign up to set email alerts
|

Ranked Schröder Trees

Abstract: In biology, a phylogenetic tree is a tool to represent the evolutionary relationship between species. Unfortunately, the classical Schröder tree model is not adapted to take into account the chronology between the branching nodes. In particular, it does not answer the question: how many different phylogenetic stories lead to the creation of n species and what is the average time to get there? In this paper, we enrich this model in two distinct ways in order to obtain two ranked tree models for phylogenetics, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It is also used as a basic building block in scheduling problems [3], as well as, e.g., in software testing [4]. In other contexts, it appears as the core problem for the generation of complex structures: we can for example cite phylogenetics [5] and bioinformatics [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also used as a basic building block in scheduling problems [3], as well as, e.g., in software testing [4]. In other contexts, it appears as the core problem for the generation of complex structures: we can for example cite phylogenetics [5] and bioinformatics [6].…”
Section: Introductionmentioning
confidence: 99%
“…This example is of interest as it indicates where the change of asymptotic behavior occurs when one varies the allowed node arities, going from binary trees with label repetitions (see [4]) to weakly increasing Schröder trees (see [5]) (with arbitrary arity of nodes).…”
Section: Strictly Monotonic Treesmentioning
confidence: 99%
“…In the study of permutations, increasing trees found usage in illuminating the behavior of local order patterns in permutations (see, for example, [6]). In biology, increasing trees find application as models of phylogenetic trees which, apart from encoding the relations between species, also encode temporal information in a way such that it encodes the history of some evolutionary process (see [5]). For a detailed and generic analysis of families increasing trees, see [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a model may serve to describe population evolution processes where each individual can give birth to two descendants independently of the other individuals. In another paper [4] we have presented an increasing model with repetitions of Schröder trees that encodes the chronology in phylogenetic trees.…”
Section: Introductionmentioning
confidence: 99%